Selection of the most Suitable Site for Dam Construction in Pishdar (AHP). District Using the Analytical Pyramid Process (AHP) (Raparin Journal of Humanities (RJH), 2026)
This study paper looks into the assessment of dam construction and the spatial distribution of suggested dams in the Pishdar District through using Geographic Information Systems (GIS) and the Analytic Hierarchy Process (AHP). Geographically speaking, Pishdar district is located in the eastern part of the Kurdistan Region and the northeastern part of Sulaymaniyah Province. However, the district extends between latitudes 36° 32′ 0″–36° 06′ 0″ N and longitudes 45° 20′ 0″–44° 54′ 0″ E, with a total area of 1,331.4 km². As a matter of fact, due to the population growth, the need for water has been increasing significantly, and on the other hand climate including rising temperatures, irregular rainfall, and frequent droughts, groundwater levels are dropping, seasonal rivers and canals are shrinking and drying up along with the Iran’s policies on governing the groundwater in the region have further made the situation worse. Most importantly, these factors highlight the necessity of this research. The objectives of this study paper are to determine suitable locations for dam construction, as well as to assess the characteristics and water storage capacities of the proposed dams and estimate the potential water inflow. At the end of our research paper, we reached a number of findings, the most important finding is that both natural and human factors in the region are favorable for dam construction. According to the AHP model, six locations were identified as the most suitable sites for dams. Their suitability levels were classified as very suitable, suitable, somewhat suitable, or less suitable. Importantly, no site was categorized as completely unsuitable for dam construction.